Ice Motion and Topography Near Margin Areas of Kamb Ice Stream, Antarctica - Scambos, Ted; Catania, Ginny; Conway, Howard; Gades, Anthony; Raymond, Charles (IEDA: US Antarctic Program Data Center, 2003)
Abstract: This data set includes ice motion and topography measurements that were taken by measuring movement and altitude of poles set in the West Antarctic Ice Shelf. The data was acquired by Global Positioning System (GPS) measurements of poles. The position of the poles was measured twice; once in 2000, and again in 2002. Movement of the poles in that time show the ice motion velocity and direction. GPS pole positions are given in latitude and longitude, and elevations are given in meters above the WGS1984 ellipsoid. The data are presented as tables in ASCII text files. Three maps of the area are included with the data tables. The National Science Foundation (NSF) funded this work under grant number OPP-9909469.